Functional, esthetic and psychological rehabilitation of a hemimaxillectomy patient with closed hollow bulb obturator - Raj K, Sounder; Gaur, Satyam; Srivastava, Rachana (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
The intraoral defects can either be congenital or acquired. The most common defects lead to an opening in maxillary antrum and nasopharynx. These defects usually affect variety of functions, including swallowing, drooling of oral secretions, speech and mastication. Esthetic, functional and psychological rehabilitation of maxillo-mandibular complex is the ultimate goal of prosthodontic treatment. The treatment of choice for such defects is the fabrication of lightweight hollow obturator prosthesis. This case report presents rehabilitation of a 58-year-old female with closed hollow bulb obturator who underwent hemi-maxillectomy with removal of floor of orbit for squamous cell carcinoma.